TO EVALUATE THE DYNAMIC DUCTILE FRACTURE OF PIPELINE STEELS BY USING INSTRUMENTED DROP WEIGHT TEAR TEST - FANG Jian; SHEN Wei; WANG Lei (Jixie qiangdu)
Derived from the hinge model for a single-edge notched bend specimen,a single specimen method to estimate CTOACof high strength and toughness pipeline steels has been established,by regression of load line displacement against the logarithmic ligament during crack extension. As to monitor the crack behavior after crack initiation directly from an instrument load-displacement curve,the linear correlation between the limit load and the square of remaining ligament width has been confirmed by applying a huge 40 k J instrumented pendulum machine onto standard pressed-notch API X80 DWTT specimens and employing key curve method,which also provides an experimental way to determine the material based parameter of A*σf,required by other CTOACestimation algorithm. As a result,in spite of the difference in the dynamic load endurance and energy consumption between full-scale and thickness-reduction sample plates,the evolution tendency of CTOA during ductile cracking are similar to each other. Moreover,CTOACvalues of both plates were determined to be constant over a given range of crack length from 25 to 40 mm within steady-state stage,independent of specimen geometry.